2009
DOI: 10.1016/j.otohns.2009.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Sclerotherapy of Branchial Cleft Cysts Using OK‐432

Abstract: These results suggest that sclerotherapy using OK-432 is an effective and safe treatment modality for BCC, especially for unilocular cysts. Sclerosing of unilocular BCC with OK-432 should therefore be considered before surgical excision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 16 publications
0
31
0
3
Order By: Relevance
“…Although surgery is also a standard treatment for a branchial cleft cyst, Kim et al [22] have highlighted the potential for the success of the OK-432 treatment by presenting results for 14 of 23 cases of a unilocular branchial cleft cyst that showed complete disappearance after injection of OK-432. Furthermore, in a study by Roh et al [23], 7 of 12 patients had a complete response to OK-432 injections after 1-3 treatments performed as those described above (i.e., 1 KE OK- 432 in 10 mL of normal saline at a volume equivalent to the amount of aspirated cyst fluid).…”
Section: Indications For Sclerotherapymentioning
confidence: 99%
“…Although surgery is also a standard treatment for a branchial cleft cyst, Kim et al [22] have highlighted the potential for the success of the OK-432 treatment by presenting results for 14 of 23 cases of a unilocular branchial cleft cyst that showed complete disappearance after injection of OK-432. Furthermore, in a study by Roh et al [23], 7 of 12 patients had a complete response to OK-432 injections after 1-3 treatments performed as those described above (i.e., 1 KE OK- 432 in 10 mL of normal saline at a volume equivalent to the amount of aspirated cyst fluid).…”
Section: Indications For Sclerotherapymentioning
confidence: 99%
“…Moreover, Kim et al [47] reported that sclerotherapy using OK-432 is an effective and safe treatment modality for branchial cleft cysts, especially if unilocular, and it should be taken into consideration before surgical excision; complete regression has been obtained in 60.8 % of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The use of endoscopic cauterization limited to the sinus tract origin as a less-invasive procedure has been noted [16]. Recently, use of sclerotherapy with OK-432 has been expanded to treat branchial cleft cysts [17]. Because of the high incidence of secondary infection of these anomalies, early excision is recommended.…”
Section: Discussionmentioning
confidence: 99%